Pengaruh Open Kinetic Chian Dan Closed Kinetic Chain Terhadap Peningkatan Aktivitas Fungsional Pada Osteoarhritis Knee Setelah Pemberian Transcutaneus Electrical Nerves Stimulation Dan Infra Red Radiation - Nugroho, Hastantyo Budi, Umi Budi Rahayu, S.Fis.M.Kes, Arif Pristianto, SSt.FT.,M.Fis (2015)
Background: Osteoarthritis is a group hetrogen condition that causes signs and symptoms associated with knee cartilage defect intergrisi and changes in the underlying bone and the joint boundary. osteoarthritis are in the process of degeneration and repair connective tissue, cartilage lining, the synovium and subchondral bone. At the time of active disease process can be a dominant one or several processes occur together in different levels of intensity. Factors that have been studied as a risk factor for knee osteoarthritis include obesity, sex, age, daily work and ginetik.untuk factor interventions improve functional activities that can be provided in the form Transcutaneus Nerves Electrical Stimulation, Infra Red Radiation and given in the form of training, which is open kinetic chain (quadriceps setting) and closed kinetic chain exercises (static bike) where this exercise can accelerate blood circulation, prevent contractures, improve muscle strength or muscle power, muscle relaxation and stability of the knee joint. Objective: This study was to determine differences in the effects of exercise open kinetic chain and closed kinetic chain to the increase of the functional activity on knee osteoarthritis. Methods: This study used a quasi eksprimental and two grop pre and post test design. The research sample of 20 people, with details of the first group of 10 people and the second group of 10 people. Measurements made with the WOMAC pain score results were analyzed using the Wilcoxon test and Mann-Whitney test. From the test data analysis shows that the open kinetic chain and closed kinetic chain to the increase of the functional activity on knee osteoarthritis, with p> 0.005. On the influence of different test to get results that open kinetic chain and closed kinetic chain no influence on the increase of functional activity in knee osteoarthritis. Keywords: closed kinetic chain, open kinetic chain, quadriceps setting, static bicycles, increased functional activity of knee joints.